ASHOKA (SARACA INDICA LINN.): A PERSUASIVE HERB FOR MENORRHAGIA - Prakash Sanjay; Dwivedi K.N (International Journal of Applied Ayurved Research, 2015)
Menorrhagia is the medical term for menstrual periods with abnormally heavy or prolonged bleeding. Although heavy menstrual bleeding is a common concern among premenopausal women, most women don’t experience blood loss severe enough to be defined as menorrhagia. Ashoka (Saraca indica Linn., Family: Fabaceae (Papilionaceae), subfamily Caesalpiniaceae. Ashoka is a tree of 6-9 meters height with glabrous branches. It is commonly known as Sorrow-less tree or Ashok tree. It is found in West Bengal, Southern India and Central and Eastern Himalaya, Western Peninsula, Burma, Ceylon and Malaya. It is well described in Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Chikitsa granthas and Nighantus. Ashoka is having Laghu, Ruksha Guna, Kashaya, Tikta Rasa, Shita Virya and Katu Vipaka. By the virtue of above properties it is kaphapittashamaka, raktastambhana, krimighna, ashmarinashana and vedanasthapana. Due to the presence of bioactive compounds tannin and catechol. Active phenolic glycoside, helmatoxylin cures urinary discharges, dyspepsia, thirst, burning sensation, diseases of the blood and effect of fatigue, enlargement of abdomen, colic, piles, bloody discharges from the uterus, internally in cases of menorrhagia, allied menstrual troubles, leucorrhoea. This review focuses on the detail botanical description, phytochemical constituents, pharmacodynamics, medicinal uses and pharmacological studies.